A System for PD Pulse Generating, Monitoring, and System Characterization - Punyavee Chaisiri; Busayapol Paophan; Peerawut Yutthagowith (My University, 2024)
This paper introduces a system for generating and measuring pulse signals used in calibrating and evaluating the performance of partial discharge detection systems. A LabVIEW-based software program has been created to control a digital oscilloscope and an arbitrary waveform generator. The program functionality includes pulse signal generation, measurement of partial discharge (PD) pulse current and charge, and characterization of PD measurement circuits in accordance with standards such as IEC 60270 and IEC 60885-3. This system can generate accurately calibrated pulse charges ranging from 2 pC to 100 pC. Additionally, it can generate a double pulse with an adjustable interval time between pulses ranging from $0.2 \mu \mathrm{s}$ to 100 $\mu s$, with the frequency of the calibrated charge signal also adjustable. Test results demonstrate that the developed system can generate calibrated pulse signals meeting standard requirements, with a charge generation tolerance of approximately 2%. Furthermore, this system offers a cost-effective alternative compared to commercial solutions. Its implementation in the High Voltage Laboratory enhances its capability to conduct partial discharge calibrations and accurately assess the characteristics of partial discharge measurement systems.
Keywords: Particle accelerators and beam dynamics; Sensor Technology and Measurement Systems; Embedded Systems and FPGA Design